Análise do uso de cartilhas e guias de orientação para construção de habitações de interesse social - Andrade, José Maria de (2014)
The housing issue in Brazil is definitely a crucial social problem in both large urban centers and its large population and also in areas where the precarious structure of housing contributes to increase poverty. Combining forces together with the organized social society might be an alternative, in this case as a community effort campaign to purchase a house. An active technical assistance for the future user along with the use of publications such as booklets, guides, manuals, technical books and other notebooks that guide through the building process might minimize the difficulties on this matter and therefore the housing issue. Nowadays a significant number of online publications provide theoretical and practical information on different topics related to housing, such as wall-building, floor, roof, cover, water facilities, sewage system, among others. This study aims to analyze the online content in order to assess its applicability. Initially, an art aspect was developed and the goal was to understand their use and their evolution. The internet is the main source of our search due to its range. It was noted during the first steps of this study that online publications are widely used in all fields and publications for the architecture and construction have advised on building practices to the society in general, however, the focus of this study is directed to those who belong to the poorest communities. It was noted that these publications have an important role in guiding the construction process, therefore they are very useful also in maintenance, renovations and future extensions